Return and volatility connectedness across global ESG stock indexes: Evidence from the time-frequency analysis - Wan, Jieru (2022)
Abstract To identify information connectedness and risk contagions among global environmental, social, and governance (ESG) markets, this dissertation uses the time and frequency domains connectedness based on time-varying parameter vector autoregressive (TVP-VAR) approaches to analyze return and volatility connectedness across global ESG stock indexes. The sample selects the eleven ESG stock indexes, including developed and developing markets, from October 1, 2007, to December 31, 2021. The empirical results show the following. First, there is a strong connectedness in return and volatility between the eleven ESG stock indexes; the ESG stock indexes of developed countries are mainly outward spillovers, while those of Asia-Pacific countries are mainly inward spillovers. Second, return connectedness is concentrated at high frequency (short term), while volatility connectedness is concentrated at low frequency (long term). Third, both return and volatility connectedness are affected by extreme events, especially the COVID-19 pandemic. However, volatility connectedness changed more dramatically than return connectedness during the pandemic. Fourth, high ESG attention leads to low return connectedness, but high volatility connectedness; the difference is that during the pandemic, ESG attention positively affects both the return and volatility connectedness across ESG stock indexes. Overall, this dissertation enriches the empirical framework for the ESG stock market, provides a reference for investors to invest in the ESG markets, and helps policymakers formulate forward-looking regulations to promote financial stability.